A dynamic network model to measure exposure diversification in the Austrian interbank market - Juraj Hledik; Riccardo Rastelli (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
We design a statistical model for measuring the homogeneity of a financial network that evolves over time. Our model focuses on the level of diversi- fication of financial institutions; that is, whether they are more inclined to distribute their assets equally among partners, or if they rather concentrate their commitments towards a limited number of institutions. Crucially, a Markov property is introduced to capture time dependencies and to make our measures comparable across time. We apply the model on an original dataset of Austrian interbank exposures. The temporal span encompasses the onset and development of the financial crisis in 2008 as well as the beginnings of the European sovereign debt crisis in 2011. Our analysis highlights an overall increasing trend for network homogeneity, whereby core banks have a tendency to distribute their market exposures more equally across their partners.
Keywords: 330; Latent Variable Models; Dynamic Networks; Austrian Interbank Market; Systemic Risk; Bayesian Inference